Guilt - Lescroart, John T. (New York : Island Books, 1997)
As chief legal counsel for the archbishop of San Francisco, Mark Dooher could not divorce his wife, therefore he murdered her. So say the police and the novel is the story of his trial, a conflict between a tenacious police detective and the powerful lawyer.
Keywords: Trials (Murder) -- Fiction; Detective and mystery fiction